2019
DOI: 10.1080/15592294.2019.1583032
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic gene methylation is associated with cognitive performance in a childhood monozygotic twin study

Abstract: Individual differences in cognitive function are due to a combination of heritable and non-heritable factors. A large body of evidence from clinical, cognitive, and pharmacological neuroscience implicates dopaminergic gene variants as modulators of cognitive functions. Neuroepigenetic studies demonstrate environmental factors also influence complex phenotypes by affecting gene expression regulation. To evaluate the mechanism of environmental influence on cognitive abilities, we examined if epigenetic regulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 79 publications
(87 reference statements)
1
15
0
Order By: Relevance
“…A recent study by Lewis et al (2019) examined the role of non-shared environmental experiences on methylation of dopaminergic genes, and the related association with cognitive task performance, in a cohort of 8 year old identical twins, thus controlling for genetic and early familial influences. They found that twin differences in DNA methylation levels of five dopaminergic genes (including COMT) predicted differences in EF.…”
Section: The Development Of the Pfcmentioning
confidence: 99%
“…A recent study by Lewis et al (2019) examined the role of non-shared environmental experiences on methylation of dopaminergic genes, and the related association with cognitive task performance, in a cohort of 8 year old identical twins, thus controlling for genetic and early familial influences. They found that twin differences in DNA methylation levels of five dopaminergic genes (including COMT) predicted differences in EF.…”
Section: The Development Of the Pfcmentioning
confidence: 99%
“…Between twins, differences in DRD4 gene methylation related to differentiation in short-term memory capacity were revealed, while differences in methylation of the DRD1, DRD2, COMT, DBH, and DAT1 genes caused individual differences in inhibition of cognitive reactions. The data obtained point to a significant impact of epigenomic modifications in the mainte-nance of complex cognitive characteristics and to a dissociative effect of methylation of dopaminergic genes in some of them [60].…”
Section: The Role Of Dna Methylation and Modification Of Histones In Development Of Cognitive Characteristicsmentioning
confidence: 89%
“…In addition, changes in chromatin modifications as a response to learning were reported to be caused by acetylation, phosphorylation, and methylation of histones [59]. In order to estimate the mechanism of environmental impact on cognitive functioning, in 2019, Lewis et al [60] conducted an analysis of the role of epigenetic regulation of dopaminergic system genes in variation of cognitive abilities. The use of a microarray to detect the methylation profile of CpG sites neighboring six dopaminergic system genes helped to analyze differences in response inhibition and memory performance in monozygotic twins.…”
Section: The Role Of Dna Methylation and Modification Of Histones In Development Of Cognitive Characteristicsmentioning
confidence: 99%
“…The etiology of sporadic neurodegenerative disorders such as Alzheimer's or Parkinson's disease is currently unknown. Epigenetics plays an important role in brain development and the establishment and loss of memory and cognition [1][2][3][4]; modulation of epigenetic factors may present a unique opportunity for treatment of central nervous system (CNS) diseases [5].…”
Section: Introductionmentioning
confidence: 99%